2018
DOI: 10.1016/j.clinre.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Primary sclerosing cholangitis response to the combination of fibrates with ursodeoxycholic acid: French–Spanish experience

Abstract: Combining UDCA with fibrates results in a significant biochemical improvement and pruritus decrease in PSC patients with incomplete response to UDCA. These results provide a rationale for larger and prospectively designed studies to establish the efficacy and safety of fibrates in PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 29 publications
5
43
0
Order By: Relevance
“…12 To date, there are no FDA-approved therapies for PSC, however, Lemoinne et al recently found improvement in cholestatic liver injury when patients with PSC were treated with the combination of Ursodiol and fibrates. 9 In our study, the total serum bile acid concentrations in control subjects were within the range reported for healthy adults. 10 In contrast, total bile acids in the Ursodiol monotherapy patients with PBC and PSC were significantly elevated but were reduced by 60% following combination with fenofibrate.…”
Section: Pro-inflammatory Cytokine Levelssupporting
confidence: 76%
See 1 more Smart Citation
“…12 To date, there are no FDA-approved therapies for PSC, however, Lemoinne et al recently found improvement in cholestatic liver injury when patients with PSC were treated with the combination of Ursodiol and fibrates. 9 In our study, the total serum bile acid concentrations in control subjects were within the range reported for healthy adults. 10 In contrast, total bile acids in the Ursodiol monotherapy patients with PBC and PSC were significantly elevated but were reduced by 60% following combination with fenofibrate.…”
Section: Pro-inflammatory Cytokine Levelssupporting
confidence: 76%
“…Pilot studies with fenofibrate and clinical studies with bezafibrate in combination with Ursodiol reduced elevated serum liver enzymes during cholestasis for patients with PBC and a subtherapeutic response to Ursodiol (reviewed in refs. 8, 9, 14). Although bile acid toxicity is a hallmark of cholestatic liver diseases, effects of fibrates on bile acid metabolism in patients with cholestasis have not been fully reported.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-series indicate potential benefits from bezafibrate also in PSC [121,122], but to date no RCT has been performed. Similar reports pertain to the PPAR-a agonist fenofibrate [123]. For the PPAR-d agonist seladelpar, however, further trial activity in PSC (and NAFLD) has been suspended due to unexpected hepatic events (in the NAFLD arm).…”
Section: Fibrates and Ppar Activationmentioning
confidence: 67%
“…In a small study of eight PSC patients only published as an abstract, fenofibrate was reported to induce significant reduction in ALP and ALT but no change in Mayo risk score at 6 months [124]. The larger French-Spanish study reported that fibrates (fenofibrate 200 mg/day or bezafibrate 400 mg/day for at least 6 months) in addition to UDCA in patients with ALP [ 1.5 9 ULN on UDCA alone, reduced ALP and ALT by 41% and 39% respectively at 3 months, as well as reduced pruritus in 20 PSC patients, with 40% of patients reaching ALP \ 1.5 9 ULN [123]. A multicenter RCT regarding the effect of bezafibrate on cholestatic itch in PBC and PSC started in 2016 and is still ongoing [125].…”
Section: Fibrates and Ppar Activationmentioning
confidence: 99%
“…PPAR agonists are now established as useful "second-line therapy" for PBC patients with insufficient UDCA response as supported by the findings of the recently published BEZURSO trial as the largest RCT supporting a beneficial role for bezafibrate, a pan-PPAR agonist [5,42]. In contrast so far, there is only a limited number of studies in PSC patients [43][44][45] and most importantly no RCT. One promising prospective study with 12-week bezafibrate treatment in 11 PSC patients showed significant improvement of AP and ALT levels and an increase of these parameters after cessation of the study medication [44].…”
Section: Ppar Agonistsmentioning
confidence: 99%